Agglutination of yeast-binding antibodies from human blood plasma products - Robbi Miguel G. Falcon; Fresthel Monica M. Climacosa; Salvador Eugenio C. Caoili (BMC Microbiology)
Abstract Background Yeasts are ubiquitous microorganisms found both endogenously within the human body and in the environment. Humoral responses against yeasts lead to the production of yeast-binding antibodies, which can agglutinate yeast cell targets. These antibodies affect the accuracy of immunodiagnostic tools employing yeast cells as in recombinant surface antigen display. Aim To improve the applicability of such tools, the study aims to determine the abundance and characterize the agglutinating behavior of yeast-binding antibodies. Methodology The study employed the use of a yeast agglutination assay to determine the prevalence of agglutination across human fresh frozen plasma samples (n = 36). The mean area of the agglutinin complex served as the basis for differentiating positive and negative samples. Indirect ELISA set-ups using protein A, protein G, and anti-IgM horseradish peroxidase conjugates were used to quantify titers and characterize the isotypes driving agglutination. Results The results of the agglutination assays and indirect ELISA revealed that the formation of agglutinin complexes was promoted by a low pH and inhibited by a high ionic strength. Coagulation factors and complement proteins did not significantly contribute to agglutination. Finally, elution of agglutinating proteins was performed and the resulting eluate was tested further for re-binding and re-agglutination with yeast cells, suggesting the presence of antibodies. Conclusion Findings from the current study suggest that antibody-mediated yeast cell agglutination driven by immunoglobulins (i.e., IgM, IgG) present in human plasma can be affected by various physicochemical factors such as pH (i.e., acidity) and ionic strength (i.e., NaCl concentration) but is independent of the activity of coagulation factors. These conditions must be carefully optimized in the development of cell-based immunoassays and yeast surface display technologies, which utilize antibody-mediated yeast agglutination.